Unequal chances on the transitional labor market: the case of the Netherlands - Govert E. Bijwaard; Justus Veenman (Institute for the Study of Labor (IZA), 2007)
The emergence of a transitional labor market offers new opportunities to workers, but at the same time bears the risk of (new) inequalities. This paper deals with unequal chances on the transitional labor market in the Netherlands, in particular for workers from the four largest immigrant groups: Turks, Moroccans, Surinamese and Antilleans. The data used are from the SPVA, the survey 'Social Position and Use of Public Utilities by Migrants' for the years 1998 and 2002. These are based on stock sampling. Since for some individuals labor market transitions occur at a very low rate, these individuals may stay in their current state till they reach the retirement age of 65. We estimate hazard rate models that account for both the stock-sampling and the possible maximum duration for the transitions from unemployment, household care and disability to employment. Then we decompose the difference in expected duration between the immigrant groups and the Dutch into the contribution of differences in observable characteristics, coefficient estimates and baseline hazard parameters. The main results of the analyses are that unequal chances exist, but to a different degree for the various groups and with variations per transition type.
Keywords: 330; Arbeitsmarktpolitik; Arbeitsmarktdiskriminierung; Ethnische Diskriminierung; Niederlande